2017
DOI: 10.1001/jamacardio.2017.3683
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mitochondrial DNA Copy Number With Cardiovascular Disease

Abstract: Mitochondrial DNA-CN was independently associated with incident CVD in 3 large prospective studies and may have potential clinical utility in improving CVD risk classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
191
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 222 publications
(216 citation statements)
references
References 26 publications
(44 reference statements)
10
191
2
2
Order By: Relevance
“…As an easily measurable and accessible proxy for mitochondrial function, mitochondrial DNA copy number (mtDNA-CN) is increasingly used to assess the role of mitochondria in disease. Several population-based studies have shown higher levels of mtDNA-CN to be associated with decreased incidence for CVD and its component parts: coronary artery disease (CAD) and stroke 2,3 ; neurodegenerative disorders such as Parkinson's and Alzheimer's 4,5 ; as well as several types of cancer including breast, kidney, liver and colorectal [6][7][8] . Furthermore, mtDNA-CN measured from peripheral blood has consistently been shown to be higher in women, decline with age, and correlate negatively with white blood cell (WBC) count [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…As an easily measurable and accessible proxy for mitochondrial function, mitochondrial DNA copy number (mtDNA-CN) is increasingly used to assess the role of mitochondria in disease. Several population-based studies have shown higher levels of mtDNA-CN to be associated with decreased incidence for CVD and its component parts: coronary artery disease (CAD) and stroke 2,3 ; neurodegenerative disorders such as Parkinson's and Alzheimer's 4,5 ; as well as several types of cancer including breast, kidney, liver and colorectal [6][7][8] . Furthermore, mtDNA-CN measured from peripheral blood has consistently been shown to be higher in women, decline with age, and correlate negatively with white blood cell (WBC) count [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…In ARIC and MESA, DNA samples were isolated from buffy coat and genotyped using Affymetrix Genome-Wide Human SNP Arrays 6.0 (the Genvisis software package [www.genvisis.org]). [11, 12, 22] Mitochondrial SNPs were collected across all samples and were signaled with high-quality mitochondrial probes. Unadjusted mtDNA-CN was determined as the median of normalized probe intensity differences across all mitochondrial SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the neuroactive ligand receptor interaction pathway has been identified as having the second highest number of atherosclerosis candidate genes of any KEGG pathway, harboring 53 atherosclerosis candidate genes (272 total genes in the pathway) [30]. This is an interesting finding given the association of mtDNA-CN with cardiovascular disease [6][7][8]. Perhaps unsurprisingly, this pathway also belongs to the class of KEGG pathways that are responsible for environmental information processing and signaling molecules/interactions.…”
Section: Dna Methylation As a Link Between Mtdna-cn And Changes In Numentioning
confidence: 99%
“…The Affymetrix Genome-Wide Human SNP 6.0 Array was used to estimate mtDNA-CN for each participant as previously described [35]. Briefly, mtDNA copy number (mtDNA-CN) was hybridization efficiency were captured via surrogate variable analysis (SVA) as previously described [7,36].…”
Section: Estimation Of Mtdna-cn From Affymetrix Human Snp 60 Arraysmentioning
confidence: 99%
See 1 more Smart Citation